(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Globally the education system after COVID-19 pandemic has undergone swingeing changes by substituting traditional class room teaching to online platforms. This research intent to reconnoitre the ideas of medical students towards digital/online education, their implication, and potentials for enhancement. A questionnaire was designed, validated, and distributed to students of Tertiary Health Care Teaching Hospital and Medical College, India. The collected data were analysed using descriptive statistics. Out of total 250 participated students, 200 were considered for the final analysis after implementing inclusion and exclusion criteria. The findings showed higher incidence of depression among third-year MBBS students. Significant statistical correlations were found between the student’s response to online teaching and evaluation with factors like attendance (0.00), health (0.009), reliable assessment (0.02) and a preference for Multiple Choice Questions over Long & short answer questions (0.003). While online medical education presents with both advantages and disadvantages. Therefore, a blended learning approach of both online and traditional education will be most effective educational strategy moving forward.